1996
DOI: 10.1038/bjc.1996.497
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent alterations of the APC and MCC genes in gastric cancers from British patients

Abstract: Summary We examined 26 gastric carcinomas from British patients for mutations of the APC gene using a single-strand conformation polymorphism (SSCP) and heteroduplex assay in conjunction with the protein truncation test (PTT). In addition, we performed loss of heterozygosity (LOH) analysis of the APC and MCC genes. We detected an inactivating somatic mutation in one gastric tumour. LOH of APC was observed in one of 12 informative cases (8%) and of MCC in two of 20 cases (10%). We thus find that alterations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Here, 18% (score) and 36% (matched pair analysis) of our cases showed an LOH at 5q, where the candidate genes APC, MCC and IRF-1 are located. As mutations of the retained allele of APC in Barrett's adenocarcinoma 43 and of MCC in gastric cancer 44 are not very frequent, there may be another target gene on 5q, such as IRF-1, which can induce apoptosis of esophageal adenocarcinoma cells in vitro. 45 However, the least common LOH area (score) in our study was 5q32-5q35.1, harboring Genetic alterations in Barrett's carcinoma T Wiech et al genes such as ECRG2, a candidate of tumor suppressor gene in esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Here, 18% (score) and 36% (matched pair analysis) of our cases showed an LOH at 5q, where the candidate genes APC, MCC and IRF-1 are located. As mutations of the retained allele of APC in Barrett's adenocarcinoma 43 and of MCC in gastric cancer 44 are not very frequent, there may be another target gene on 5q, such as IRF-1, which can induce apoptosis of esophageal adenocarcinoma cells in vitro. 45 However, the least common LOH area (score) in our study was 5q32-5q35.1, harboring Genetic alterations in Barrett's carcinoma T Wiech et al genes such as ECRG2, a candidate of tumor suppressor gene in esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Observations from colorectal and gastric cancers suggest that despite the high frequency of loss of heterozygosity of the MCC gene, mutation of the retained MCC allele is uncommon. 75,76 This suggests that MCC does not function as a tumor suppressor gene in gastrointestinal malignancies. IFNA, interferon-alfa gene; NF1, neurofibromatosis gene; CSF3, colony stimulating factor 3; erbB-2, member of epidermal growth factor receptor family; ITB4, integrin-beta 4; MSH3, DNA mismatch repair gene; Rb, retinoblastoma; VHL, von Hippel Lindau gene; PPAR␥, peroxidase proliferator-activated receptor-␥; MCC, mutated in colorectal cancer; APC, adenomatous polyposis coli; IRF-1, interferon regulatory factor 1; TOC, tylosis esophageal cancer gene; DCC, deleted in colorectal carcinoma; DPC4, deleted in pancreatic carcinoma, locus 4; TP53, p53 tumor suppressor gene; BRCA1, breast cancer gene; WT2, Wilms' tumor suppressor gene; H19, gene involved in genomic imprinting; p57KIP2, a cyclin-dependent kinase inhibitor; HIC1, hypermethylated in cancer; OVCA1/2, ovarian cancer tumor suppressor genes 1 and 2; GH, growth hormone gene; Smad-2, signal transduction molecule involved in TGF-␤ signaling pathway.…”
Section: Chromosome 5qmentioning
confidence: 99%
“…For example, Sasaki et al [30] found no β-catenin mutation in gastric cancer tissues, whereas they observed nuclear β-catenin staining in 23% of the same cancer tissues. Also, truncation mutations of APC gene were rarely detected in gastric cancer tissues [31]. AXIN1 mutation is observed frequently in hepatocellular carcinomas [9], but it has not been reported in gastric cancers.…”
Section: Discussionmentioning
confidence: 99%